2021
DOI: 10.2147/jir.s292263
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Attenuates Ischemia/Reperfusion-Induced Myocardial Inflammation and Apoptosis Through Inhibiting Endoplasmic Reticulum Stress Signaling

Abstract: Background Endoplasmic reticulum stress (ERS)-mediated myocardial inflammation and apoptosis plays an important role in myocardial ischemia/reperfusion (I/R) injury. Dexmedetomidine has been used clinically with sedative, analgesic, and anti-inflammatory properties. This study aimed to determine the effects of dexmedetomidine pretreatment on inflammation, apoptosis, and the expression of ERS signaling during myocardial I/R injury. Methods Rats underwent myocardial ische… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 38 publications
1
20
0
1
Order By: Relevance
“…As shown in the present study, DEX alleviated neuroinflammation in mouse TBI models. Additionally, DEX directly regulates several cell death models (22,25,(48)(49)(50)(51). According to Gao et al (49), DEX induces the expression of the neuroglobin protein in hippocampal tissues and then inhibits neuronal apoptosis through the mitochondrial pathway.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in the present study, DEX alleviated neuroinflammation in mouse TBI models. Additionally, DEX directly regulates several cell death models (22,25,(48)(49)(50)(51). According to Gao et al (49), DEX induces the expression of the neuroglobin protein in hippocampal tissues and then inhibits neuronal apoptosis through the mitochondrial pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were incubated at 37 °C in an atmosphere of 5% CO 2 , and grown to 80% confluence before use. For oxygen glucose deprivation/ reoxygenation (OGD/R) treatment is the same as the description of our previous research (Yang et al, 2021b). Briefly, HEK293T were cultured in an anaerobic chamber containing 95% N 2 and 5% CO 2 for 6 h and then reoxygenated for 6 h to induce OGD/R condition.…”
Section: Establishment Of Renal Ischemia-reperfusion Model Cell Cultu...mentioning
confidence: 99%
“…The signaling mechanism in which autophagy induces its effects on the endoplasmic reticulum remains an area for future research. However, a more recent study showed that the use of a highly selective agonist of α2-adrenergic receptors, dexmedetomidine improves myocardiocyte ischemic/reperfusion injury by down-regulation of the endoplasmic reticulum stress signaling pathway that includes glucose-regulated protein 78 (GRP78), protein kinase R-like endoplasmic reticulum kinase (PERK), homologous protein C/EBP (CHOP), inositol-requiring protein 1 (IRE1), and activating transcription factor 6 (ATF6) [50].…”
Section: Autophagy Of the Endoplasmic Reticulum Of Myocardiocytesmentioning
confidence: 99%